Studi Kelayakan Bisnis Pada UMKM Happy Bento Cake - Eka Raysha, Njawa Meidinar; Sidik, Fajar; Lajai Madam, Sri Yulandasari; Perwito, Perwito (Universitas Serambi Mekkah, 2024)
This business feasibility study aims to analyze the business potential of Happy Cake, which sells bento cakes, using descriptive qualitative research methods. Data were collected through analysis of market and marketing, operational and production, human resources (HR), financial, and legal aspects. The results showed that the business has good prospects, with high demand from young people and university students. Marketing through online platforms has proven effective in reaching the target market. In the operational aspect, production capacity needs to be increased to meet the growing demand. In the financial aspect, the business shows promising profit potential with affordable start-up capital. Legally, the business can run by complying with applicable regulations. Overall, Happy Cake is considered feasible to establish and has good growth potential.